2019
DOI: 10.1371/journal.pone.0216231
|View full text |Cite
|
Sign up to set email alerts
|

A modest protective association between pet ownership and cardiovascular diseases: A systematic review and meta-analysis

Abstract: Purpose Investigate the relationship between pet ownership and cardiovascular (CV) outcomes. Methods We searched the PubMed, Ovid EMBASE, Cumulative Index to Nursing and Allied Health Literature, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials databases up to August 2018. Eligible publications examining the association between pet ownership and all-cause and CV mortality (primary outcomes) and risks of cardiovascular disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…The earliest health issues addressed outside of the elderly population were focused on cardiovascular problems, which were prevalent and easy to assess, and the first AAI article to appear in a recognized peer-reviewed medical journal demonstrated that animal ownership improved the one-year survival rate after a cardiovascular event [30]. Over the years, there has been much literature in this area of study [31,32,33,34,35,36]. Now, there is an ever-growing interest to have animals facilitate activity, especially walking [37,38,39].…”
Section: The Need For Research and Evidence: Connecting The Dots Fmentioning
confidence: 99%
“…The earliest health issues addressed outside of the elderly population were focused on cardiovascular problems, which were prevalent and easy to assess, and the first AAI article to appear in a recognized peer-reviewed medical journal demonstrated that animal ownership improved the one-year survival rate after a cardiovascular event [30]. Over the years, there has been much literature in this area of study [31,32,33,34,35,36]. Now, there is an ever-growing interest to have animals facilitate activity, especially walking [37,38,39].…”
Section: The Need For Research and Evidence: Connecting The Dots Fmentioning
confidence: 99%
“…Previous data have indicated that factors, such as owning a pet, seem to affect the gut microbiota composition [ 30 ]. Additionally, it has also been described that pet ownership is associated with a lower risk of suffering CVD, mainly by providing social support and motivation for physical activity [ 4 , 5 ]. Despite this increasing knowledge, the potential improvement in the gut microbiota profile associated with pet ownership in cardiovascular disease patients has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological conditions, such as age, ethnicity, gender, diet, physical activity, amongst others, have been linked to MetS [ 3 ]. However, the relationship between the risk of suffering it and owning pets has not been sufficiently studied, although being in contact with pets has been considered a protective factor against CVD [ 4 , 5 ] and other diseases in children, including allergies and obesity [ 6 , 7 ]. In fact, some evidence suggests that this protection might be due to favorable changes in the intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data have indicated that factors such owning a pet seems to affect gut microbiota composition [28]. Additionally, it has also been described that pet ownership is associated to lower risk of suffering CVD, mainly by providing social support and motivation for physical activity [3,4]. Despite this increasing knowledge, the potential improvement in gut microbiota pro le associated to pet ownership in cardiovascular disease patients has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological conditions, such as age, ethnicity, gender, diet, physical activity, amongst others, have been linked to MetS [2]. However, the relationship between the risk of suffering it and owning pets has not been su ciently studied, although being in contact with pets has been considered a protective factor against CVD [3,4] and other diseases in children, including allergies and obesity [5,6]. In fact, some evidences suggest that this protection it might be due to favourable changes in the intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%